Examination of Football Players’ Perfectionism Features and Subjective Stress Perceptions - Çağrı Hamdi Erdoğan; Ramazan Topuz; Ziya Bahadır (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to determine the perfectionism characteristics and subjective stress perceptions of football players. In this respect, subjective stress perceptions and perfectionism characteristics of football players were examined according to variables such as age, marital status, educational level, income level, football background and position. The research was conducted with the descriptive survey model. Randomly selected 279 amateur football players, who actively played football in the super group and the first group during the 2017-2018 seasons in Konya province, participated in the study. "Multidimensional Perfectionism Scale” and “Perceived Stress Scale” were used as the data collection tools. SPSS program was used in the analysis of the data. According to the results of the research, subjective stress perceptions and perfectionism features of the football players were determined as "midlevel". In addition, a negative significant relationship was found between the football players' perfectionism features and subjective stress perception. Perfectionism features of the football players significantly differed based on their football backgrounds, gender, age, educational level, income level and the position they played. Subjective stress perceptions of them did not show any significant difference concerning gender, age, educational level, income level, football background and position.